Urban Family Planning in Low- and Middle-Income Countries: A Critical Scoping Review - Duminy, James; Cleland, John; Harpham, Trudy; Montgomery, Mark R.; Parnell, Susan; Speizer, Ilene S. (Frontiers in Global Women's Health, 2021)
Health agendas for low- and middle-income countries (LMICs) should embrace and afford greater priority to urban family planning to help achieve a number of the global Sustainable Development Goals. The urgency of doing so is heightened by emerging evidence of urban fertility stalls and reversals in some sub-Saharan African contexts as well as the significance of natural increase over migration in driving rapid urban growth. Moreover, there is new evidence from evaluations of large programmatic interventions focused on urban family planning that suggest ways to inform future programmes and policies that are adapted to local contexts. We present the key dimensions and challenges of urban growth in LMICs, offer a critical scoping review of recent research findings on urban family planning and fertility dynamics, and highlight priorities for future research.